Use of Alternative Fuels in the Cement Sector in Senegal : Opportunities, Challenges and Solutions - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
Rapid urbanization in emerging markets has created new challenges for economic development and poverty reduction. The need for more buildings, transport and other infrastructure has boosted demand for construction materials and especially cement, making it the centerpiece of the urban development agenda. In Sub-Saharan Africa, consumption of cement is expected to continue to grow over the coming decade. To meet this demand, over a dozen new kilns were launched in Africa in recent years. At the same time, increasing output poses challenges for cement producers, who invest significantly in sourcing energy and fuel, primarily coal or natural gas. An alternative approach is to improve efficiency and implement new technologies, such as waste heat recovery and renewable energy – and utilize alternative fuels, which are already used by major players in the cement sector globally. In IFC, a member of the World Bank Group, we have an investment portfolio in cement and construction materials of over $4.2 billion, and vast global experience in developing innovative solutions and leveraging best practices. For instance, we identify waste heat recovery opportunities as well as international best practices in the use of alternative fuels at cement plants. This report summarizes the outcomes of the assessment of alternative fuel opportunities in the country, with a focus on sourcing energy from municipal, commercial and similar waste, tires, sewage sludge and agricultural residue. It outlines the total potential as well as possible project models, involving linkages between the cement and waste management sectors. IFC has also assessed market barriers and offered measures that aim to increase the uptake of the use of alternative fuels.